PENGARUH PEMERIKSAAN PAJAK, PENAGIHAN PAJAK, DAN KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK STUDI KASUS PADA KPP PRATAMA RABA BIMA TAHUN 2012-2015 - Sunarto Sunarto; Arfaningsi Muhammad (AKUNTANSI DEWANTARA, 2018)
This research is aimed to determine the influence of tax examination, tax collection, and taxpayer pursuence in simultaneously as well as partially toward tax reciept. The population of research were taken from all of tax receipt realization report which is published by Pratama Raba Bima Tax Office (KPP). Purposive sampling technique is using to collect the samples. It is from taxpayer that published by assessment tax (SKP), tax collection (STP), and annual tax return (SPT) of KKP Pratama Raba Bima during the period of 2012 – 2015. The data will be tested with statistic, classic assumption, and analysis by using multiple regression analysis method. The result of this research show that tax examination, tax collection, and taxpayer pursuence has positive influence in simultaneously toward tax reciept. P-value is 0,000. It means that the p-value is smaller to determinable value which is 5 %. Tax examination and taxpayer pursuence has no influence in partially toward tax reciept, because known that p-value > α (0,121 and 0,263 < 0,05) means 0,121 and 0,263 are smaller to 0,05. Besides tax collection is known p-value < α (0,034 < 0,05) means 0,034 is smaller to 0,05 that is significant. Thereby, it can be conclude that tax collection in partially has positive influence toward tax reciept. So, tax examination, tax collection, and taxpayer pursuence has 39,7 % influence toward tax reciept. Besides 60,3 % of support remaining come from other factors that influence of tax reciept. Password : tax examination, tax collection, taxpayer pursuence, tax reciept